Failed medical termination of pregnancy associated with implantation in a non-communicating uterine horn. Issue 3 (1st July 2004) - Bradshaw, Helen; Stewart, Peter
Abstract : A failed medical termination of pregnancy at 16 weeks' gestation proved to be due to a uterine malformation. Delay in diagnosis resulted in uterine rupture and the need for an emergency laparotomy. Recommendations are made for earlier diagnosis.